Stimulate social interaction in the public realm / Ahmad Faiq Abd Wahid ... [et al.] - Abd Wahid, Ahmad Faiq; Hanapi, Nurul Liyana; Zaharin, Puteri Mayang Bahjah; Ahmad Basirun, Maisarah; Hilmi, Fariz (UiTM Press, 2024)
Public realms are viewed as social gatherings between communities where engagement takes place. However, the concept of public realms between Islamic and Westerns remains to be seen, and the similarities and differences in views might lead to different social interactions among them. Thus, this study evaluates the social interaction perspective between Islamic and Western beliefs in public realms. The method employed in this paper is the analysis of literature from previous studies to evaluate social engagement in public realms. Based on Islamic and Western worldviews, this paper demonstrates that 'third places' of social and behavioural characteristics involving inclusivity and social comfort are revealed through empirical fieldwork on social interaction among people in public and semi-public spaces. The main key factor focuses on how these two worldviews define and characterise social interaction and the principles in their spatial organisation that must be considered to achieve social interaction in the public realm. Finally, the findings provide hope for urban design practice by providing fresh insights into creating more dynamic and inclusive public areas.